2019
DOI: 10.1002/hyp.13418
|View full text |Cite
|
Sign up to set email alerts
|

Possible soil tension controls on the isotopic equilibrium fractionation factor for evaporation from soil

Abstract: The stable isotopes of hydrogen and oxygen (δ 2 H and δ 18 O) are useful conservative tracers for tracking the movement of water in soil. But although the tracking of water infiltrating through the soil profile and its movement as run-off and groundwater recharge are well developed, water movement through the soil can also include evaporative fractionation. Soil water fractionation factors have, until now, been largely empirical. Unlike open water evaporation where temperature, humidity, and vapour pressure gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 41 publications
0
40
1
Order By: Relevance
“…3). Samples dried at 105°C plotted along the same regression line as found by Gaj and McDonnell, (2019), considering all values below pF 5. Values above pF 5 showed a decrease in α x − y only for the samples dried at 105°C.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…3). Samples dried at 105°C plotted along the same regression line as found by Gaj and McDonnell, (2019), considering all values below pF 5. Values above pF 5 showed a decrease in α x − y only for the samples dried at 105°C.…”
Section: Resultsmentioning
confidence: 86%
“…All values plot within the calculated α values using the Kelvin equation. A regression line found by Gaj and McDonnell (2019) is also indicated (dashed gray). Heat treatment of the field samples at 105°C resulted in higher slopes of α 18 O.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaj et al () showed that the degree of transport, mixing and fractionation of water stable isotopes within the unsaturated zone under drought is controlled by the composition of the biogeochemical interface, soil tension, and wettability. Especially the use of stable isotope signatures of soil water and water vapour at the dry end of the water retention curve (around wilting point) is largely unexplored, but nevertheless important, because these dry conditions occur preferentially at the shallow soil depths, where evaporation into the atmosphere occurs (Gaj & McDonnell, ). However, the strength of the relationship between mobility and isotopic composition remains poorly constrained (Shuler, ).…”
Section: Discussionmentioning
confidence: 99%
“…McDonnell () suggested discrete isotopic sampling along the soil moisture release curve to tackle this phenomenon. Some have started the evaluation of this phenomenon suggesting that soil water retention characteristics in the future may be a critical component influencing the soil water isotopic composition (Gaj & McDonnell, ), and others are attempting to model bulk water processes versus mobile water processes to further explain fractionation effects and delineate the water pools (Sprenger et al, ).…”
Section: Discussionmentioning
confidence: 99%